Enhanced Nutrition Programs to Rehabilitate Freeze-stressed Citrus Trees in Subtropical Regions - D. A. De Leon; S. D. Nelson; M. Sétamou; A. Bhandari; E. Zamora; A. Zaragoza; M. C. Donato; J. Reyes-Cabrera (HortScience)
Citrus spp. trees are not fully dormant during the winter months in the northern hemisphere; therefore, they are susceptible to sporadic freeze events of various magnitudes that could decline tree productivity or be lethal. In Feb 2021, winter storm Uri produced freezing air temperatures for nearly 72 hours, which created several degrees of injuries to citrus orchards in southern Texas. Producers in the area implemented combinations of multiple horticultural practices aimed at remediating injuries from the cold spell to stimulate root and tree recovery. However, there is a gap in our understanding of how practices such as compost application (CA) combined with varying rates of nitrogen (N) might facilitate tree recovery. Therefore, we conducted a 2-year field experiment using two CAs as soil amendments in combination with three N rates (112, 168, and 224 kg·ha−1 N) to evaluate fruit yield and internal quality, root growth, and recovery of ‘Rio Red’ grapefruits (Citrus ×paradisi Macf.) and ‘Marrs’ sweet oranges (Citrus sinensis). The yields of both crops exhibited modest improvement with CA in 2022; however, it was nonsignificant. Moreover, CA elicited more beneficial effects than N rates alone when rehabilitating trees and improving fruit internal quality after freezing events. Grapefruit brix was 4% higher in fruits harvested from trees treated with compost, and grapefruit roots exhibited a two-fold dry weight increment with CA. Sweet oranges from trees in the CA treatment had 22% lower acidity compared with that of untreated trees. Overall, our results indicate that citrus producers in southern Texas and other subtropical citrus-producing regions might facilitate the rehabilitation of tree injuries attributed to mild to moderate freeze events with moderate financial gains with the timely application of compost, which enhanced tree fitness and ameliorated fruit productivity declines during subsequent harvests.